High‐Temperature Compressive Behavior of Refractory Alumina–Niobium Composite Material. Issue 8 (11th May 2022) - Günay, Gökhan; Zienert, Tilo; Endler, Dirk; Aneziris, Christos G.; Biermann, Horst; Weidner, Anja
Abstract : The development of coarse‐grained refractory composites combining refractory ceramics with refractory metals provides new approaches for high‐temperature applications. In particular, coarse‐grained Nb‐Al2 O3 composites are widely interested due to their promising functional properties such as high thermal shock resistance, low shrinkage and good electrical conductivity. In order to identify and release the potential of these materials in advanced applications, their mechanical behavior should be evaluated. This study presents room‐ and high‐temperature compression behavior up to 1500 °C of Nb‐Al2 O3 refractory composites manufactured via castable and extrusion technology. The influences of production method, particle size, open porosity as well as temperature and strain rate are discussed. For comparison, pure niobium and alumina specimens are used as reference materials. The results indicate that Nb‐Al2 O3 refractory composites show high ductility at high temperatures. This behavior is also verified with microstructural investigations by scanning electron microscope (SEM). Abstract : High temperature mechanical behavior of Nb‐Al2 O3 composites (60 wt% Nb, 40 wt% Al2 O3 ) manufactured in different technologies is investigated up to 1500 °C under compression. Higher plasticity is observed of all manufactured composite variants at high‐temperatures. Based on mechanical and deformation behavior, these composites are possible candidates for the applications of sandwich/core‐shell structures.